Biocentris, sustainability and alterity ethics - Grubba, Leilane Serratine; Pellenz, Mayara (Revista Brasileira de Direito Animal, 2021)
The research aims to analyze the connection between sustainability and biocentrism in the construction of an ethics of Alterity, highlighting its approximations and differences. The human being uses the environment for his development – economic, social and technological. However, a change is needed to reduce the unrestrained consumption of the nature elements, as this lack of control can lead to the extinction of the human species and other forms of life that inhabit the planet. One of the solutions for the preservation of nature is to put sustainability into practice individually, thinking about the collective. In This article, a wide qualitative research of bibliographic character was carried out, using deductive reasoning.